Dietary Supplements: Foods, Medicines, or Both? A Controversial Designation with Unspecific Legislation - Pereira, Carla; Barros, Lillian; C.F.R. Ferreira, Isabel (Current Pharmaceutical Design, 2017)
Background: Dietary supplements have been widely used among the United States of America (USA) and the European Union (EU) population not only as a form of nutrition but also for medicinal purposes. Still, the legislation regulating these supplements remains unclear due to the fact that they can be considered as foodstuffs and/or medicinal products depending on various factors. Methods: The present review article intends to provide information concerning the variations on the definition of dietary supplements, the allowable substances on it, as well as the marketing and labelling requirements among the USA and the EU legislation. Results/Conclusions: In fact, several discrepancies can be found between regulations in the USA (mainly regulated by the Food and Drugs Administration) and in the EU (principally regulated by the Food Supplements Directive or by the Directive 2001/83/EC), and even between the different Member States of the EU, with the main differences observed in new products marketing requirements.
Keywords: Dietary supplements